Penganggaran dan pengawalan ralat dalam kaedah HaM-4(4) untuk penyelesaian masalah nilai awal - Yaacob, Nazeeruddin; Sanugi, Bahrom (Faculty of Science, 1994)
In this papaer a new fourth order formula based on harmonic and arithmatic means is formulated. The formula when used with the Harmonic-Rungge-Kutta formula is capable of estimating the local truncution error in solving initial value problems. The absolute stability region of the method is also studied. The numerical results presented showed the effectiveness of the method